A feasibility study of ergospace: Ergonomically designed chairs showroom office fixtures - Alano, Samantha Nicole B., Javierto, Rosenda Mae R., Molon, Mirjan Julia Valen F., Reyes, James Andrei T., Suarez, Kyle Justin N. 4 0 16; 5
u
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2